A comparison study of three fluxing agents in promoting properties and environmental safety of bricks incorporating hazardous waste. (10th April 2021) - Mao, Linqiang; Zeng, Man; Peng, Mingguo; Hu, Linchao; Zhang, Wenyi
Abstract: The incorporation of hazardous solid waste in fired bricks fabrication is a viable way. However, the physical and mechanical properties of products were negatively influenced due to the involvement of hazardous solid waste. Three fluxing agents, waste glass powder (WGP), Na-feldspar and K-feldspar, were introduced in this study to eliminate these negative influences. Physical and mechanical properties were tested by standard method. Microstructure and pore structure of bricks were conducted by Scanning Electron Microscopy (SEM) and nitrogen adsorption and desorption isotherm. The change in mineral phase was detected by X-Ray Diffraction (XRD). The leaching toxicity of heavy metals were carried out by Toxicity Characteristic Leaching Procedure (TCLP) and Netherlands tank leaching test. The introduction of fluxing agents can greatly promote effectively compressive strength and decline water absorption. When 30 wt% (weight percent) of fluxing agents are added, water absorption reduced by more than 50%, and compressive strength increased by more than one time. XRD and SEM analysis showed that fluxing agents can promote the formation of glass-ceramic phase, which were mainly formed by the self-melting reaction of fluxing agents and the interaction with silicon-aluminium oxides. These dense glass phases could reduce the porosity and promote the compactness of microstructure. The formation of glass-ceramic phases could also reduce the leachability risk of heavy metals. Combing with properties of brick and price of fluxing agents, WGP is considered to be more suitable for improving properties of fired bricks containing hazardous waste. This study could provide some useful parameters and knowledge for improving properties and leaching toxicity risk when hazardous wastes were utilized in the production of fired brick. Graphical abstract: Image 1 Highlights: Fluxing agents can reduce water absorption substantially. Fluxing agents can promote compressive strength remarkably. Microstructure become homogeneous and dense due to fluxing agents Fluxing agents can decrease leachability of heavy metals